Comparison of Aerodynamics and Flight performance of Fixed Wing Solar Powered Unmanned Aerial Vehicle when separate lift and thrust Vertical Take-Off and Landing system is installed - Suracharttumrongrat, Aim; Kampoon, Janewit (Engineering and Technology Horizons, 2023)
The objective of this research paper is to analyze the effects of installing a separate Lift and Thrust vertical takeoff system for fixed-wing solar powered UAVs in terms of flight performance changes. This research article uses a prototype aircraft in this study, which is a fixed-wing aircraft powered by an electrical system and equipped with a solar system. There are 2 types of designs, namely the type with installation and without installation of the Vertical Take-Off and Landing system which the vertical take-off and landing aircraft compared to the normal configuration will weigh 42.48% more and have a zero-lift drag coefficient of 67.1% more. The initial step involves creating an aircraft model in the XFLR5 software to assess the lift and drag coefficients and compare them with the wind tunnel test results. Subsequently, the software analysis findings are used to evaluate the flight performance of both aircraft configuration, as well as to identify the performance changes that occur when the VTOL system is installed. The outcomes align with expectations, installing a VTOL system leads to a significant reduce in flight performance, In particular, the Endurance and maximum range of vertical take-off aircraft are only 41.55% and 43.43% of normal aircraft and for solar-powered systems. The vertical takeoff has the Endurance and range is 31.46% and 32.06% of normal aircraft equipped with solar systems. which can be distinctly contrasted with the performance of aircraft in various aspects. However, these compromises are made in exchange for the capability to take off and land vertically.